2008
DOI: 10.1016/j.freeradbiomed.2007.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Novel redox-dependent regulation of NOX5 by the tyrosine kinase c-Abl

Abstract: We investigated the mechanism of H 2 O 2 activation of the Ca 2+ -regulated NADPH oxidase NOX5. H 2 O 2 induced a transient, dose-dependent increase in superoxide production in K562 cells expressing NOX5. Confocal studies demonstrated that the initial calcium influx generated by H 2 O 2 is amplified by a feedback mechanism involving NOX5-dependent superoxide production and H 2 O 2 . H 2 O 2 -NOX5 activation was inhibited by extracellular Ca2+ chelators, a pharmacological inhibitor of cAbl, and over-expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
89
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 46 publications
(52 reference statements)
5
89
1
Order By: Relevance
“…5). The ability of the proto-oncogenic kinase C-able to increase Nox5 activity also suggests that it may play an important role in cancers such as leukemia (22). From these findings, it is clear that Nox5 is expressed in certain types of cancers and can contribute to the increased proliferation seen in these cells.…”
Section: Nox5 and Regulation Of Cellular Functionmentioning
confidence: 94%
See 1 more Smart Citation
“…5). The ability of the proto-oncogenic kinase C-able to increase Nox5 activity also suggests that it may play an important role in cancers such as leukemia (22). From these findings, it is clear that Nox5 is expressed in certain types of cancers and can contribute to the increased proliferation seen in these cells.…”
Section: Nox5 and Regulation Of Cellular Functionmentioning
confidence: 94%
“…The proto-oncogenic tyrosine kinase, c-abl, can bind to and increase Nox5 activity via a calciumsensitive, hydrogen peroxide-dependent signaling pathway (22). The functional significance of this with regard to cancer, in particularly chronic myelogenous leukemia, is not well understood.…”
Section: Nox5 and Regulation Of Cellular Functionmentioning
confidence: 99%
“…El Jamali et al, on the other hand, reported that H 2 O 2 induced O 2 -production in K562 cells expressing NOX5. This activation was mediated by Ca 2+ -dependent membrane translocation of c-Abl non-receptor tyrosine kinase, and association of NOX5 with c-Abl was suggested (84).…”
Section: Nox5mentioning
confidence: 97%
“…Hsp90 binds to and regulates Nox5 protein stability (56,126,33). In human endothelial cells (ECs), siRNA-mediated Nox5 knockdown reduced Ang II stimulated ERK1/2 activation, but not that of p38 MAPK or JNK (56 (135,203).…”
Section: Nox5mentioning
confidence: 99%